The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1016/j.jaad.2013.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D concentration does not correlate with atopic dermatitis severity

Abstract: Background An inverse correlation between serum 25-hydroxyvitamin D concentration and atopic dermatitis (AD) severity has been suggested. Objective To determine if a statistically significant relationship exists between serum 25-hydroxyvitamin D concentration and AD severity. Methods A cross-sectional study was conducted of patients with AD aged 1–18 years. An objective Severity Scoring of Atopic Dermatitis (SCORAD) and a serum 25-hydroxyvitamin D concentration were measured for each subject. Statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
6
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 35 publications
(39 reference statements)
5
44
6
4
Order By: Relevance
“…This is in agreement with the study by other authors [12][13][14][15], who linked vitamin D deficiency to prevalence of AD and other allergic diseases.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This is in agreement with the study by other authors [12][13][14][15], who linked vitamin D deficiency to prevalence of AD and other allergic diseases.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, we found that 66.7% of the AD patients had insufficient or deficient vitamin D; this is in accordance with the results of other studies [13][14][15] but with different percentages ranging from 61 to 82.5%. This variation in the percentages of patients with insufficient or deficient vitamin D may be due to the great variation in the clinical severity of AD in each study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Samochocki et al [32] found that the mean serum concentration of 25(OH)D3 was not significantly different between patients with AD and control subjects. Studies by Chiu et al [33] and Han et al[34] showed that although VD levels were lower in AD patients than in HCs, there was no correlation between VD levels and AD. A few plausible explanations have been suggested to explain these contrary results about the relationship between VD and AD.…”
Section: Discussionmentioning
confidence: 99%
“…26 In contrast to the already mentioned results, some studies did not find any relationship between vitamin D concentration and AD severity. 23,27 In a cross-sectional study conducted in 97 children with AD, Chiu et al 27 found no correlation between levels of vitamin D and SCORAD (P = 0.99). More recently, Hata et al, 23 in a randomized, placebo-controlled, double-blind study conducted on 76 atopic, nonatopic, and psoriatic adult patients, also reported no vitamin D influence on the AD severity both before and after supplementation.…”
Section: The Relationship Between Vitamin D Levels and The Severity Omentioning
confidence: 98%